Peran Manajemen Perubahan Pada Akuntansi Manajemen Strategis Akibat Virus Corona - Varhan Ardiansyah; Novta Fardhika; Siti Aisyah; Agus Wahyudi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
The corona Virus or Covid-19 is forcing people to change their lifestyles, and the presence of the corona virus threatens the stability of the Indonesian economy. Some companies have achieved efficiency gains, from salary cuts to layoff decisions. Introduce a system of cancellation of employment contracts. The state of the home economy has a great impact on the lower middle class, so it is necessary to make lifestyle changes and bad habits to spend money on things that are not important to you. But to survive in difficult times, it is necessary to apply some coping strategies for life. It is about establishing spending management strategies to deal with uncertainty regarding when the epidemic will end. In addition, to achieve this, the ability to maintain economic stability is needed. it is necessary to decide what strategy to take to start developing new concepts for the future and ensure the survival of the company in the future. This crisis planning includes understanding where the basic focus is in the store network, planning crisis inventory in the event of a supply shortage, and identifying alternative supplies. In addition, by establishing a policy of working from home and remote meetings and adhering to health protocols, you can ensure that employees in crucial positions that contribute to the success of your business can continue to work more flexibly. This is because the government and the community can avoid deterioration and losses due to the negative impact of the corona virus on the household economy and local economy by working together on projects that benefit both parties. Descriptive and validation methods are used in the study, and the analysis tool is Structural Equation Modeling (SEM, Lisrel). Given the current corona virus has a significant impact on the Indonesian economy, the findings indicate that the role of Change Management in strategic management accounting is very influential